Lower Limb Radiology Tutorial Designed to Enhance Anatomy Education and Medical Application of Anatomy - Michelle Lazarus; Lindsay Smith; Allison Hoover; Pamela Brian (Association of American Medical Colleges, 2013)
Abstract Introduction This tutorial was developed to cover the anatomy, imaging, and clinical significance of a single anatomical region: the lower limb. It was developed through a close collaboration between medical students (following their participation in anatomy), a clinical radiologist, and an anatomist. Methods The tutorial consists of various radiologic image types (ranging from plain films to MR images) structural labeling, and also incorporates clinical correlations. This tutorial was developed to provide earlier contact with clinical anatomy and to enhance the formal opportunity for student self-study beyond what most current radiology tutorials allow; many of the slides within the tutorial contain opportunities for student self-reflection through animated question and answer pop-ups. The authors feel that this tutorial offers a unique niche within the field of anatomy education because of the combination of methods used to develop the tutorial and the types of information included within this tutorial. Results The preliminary study population consisted of volunteer first-year medical students participating in the Structural Basis of Medical Practice course at The Pennsylvania State College of Medicine during the 2012-2013 academic year. Students were randomly divided into intervention and control groups for evaluation the efficacy of these tutorials. The control group received only basic anatomy instruction. The intervention groups received basic anatomy instruction plus access to the lower limb tutorial access for up to one hour. Anatomical knowledge, in both groups, was evaluated through written assessments prior to beginning the anatomy course and following the period of tutorial access provided to the intervention groups. Pretutorial and posttutorial assessments were evaluated in a blind manner. The mean difference in assessment scores between intervention and control groups was established with results stratified for those without prior anatomy experience. Tutorial access positively impacted overall anatomy knowledge. Discussion The most significant impact of these tutorials on learning was in structure identification of radiologic images. In addition, self-efficacy subjective studies revealed that students overwhelmingly felt that this tutorial was beneficial for their learning of anatomy and that that they would use this type of tutorial at least weekly throughout their medical school education. This study provides evidence that this clinical imaging/lower limb tutorial is a viable adjunct in enhancing anatomy education.